6 – BENZYLAMINOPURINE INDUCES HIGH-FREQUENCY MULTIPLICATION IN VULNERABLE Curcuma pseudomontana J. Graham.: A POTENTIAL EX VIVO CONSERVATION TOOL - Gayatri Vaze; Pramod Hurkadale; Harsha Hegde (BIOTROPIA, 2024)
A rapid high-frequency multiplication protocol is designed for Curcuma pseudomontana J. Graham, belonging to the family Zingiberaceae, an endemic species to the Western Ghats of India. The IUCN Red List of Threatened Taxa mentions this species as vulnerable due to multiple underlying causes. The Plant is extensively used in traditional and tribal medicine. The species has suffered habitat loss due to uncontrolled use for tribal medicine leading to a 30% loss in the last decade. This study is planned with a specific objective to conserve the species, and this is the first-ever report of micropropagation of Curcuma pseudomontana J. Graham using in vitro multiplication. An efficient rapid protocol for Micropropagation is developed using rhizome bud explants. The explants are transferred from MS basal medium onto the MS medium fortified with BAP, KN, TDZ at a varying concentration range. The maximum shoot induction is observed in MS medium enriched with BAP 2mg L-1resulting in 9.66 ±2.08 number of shoots per explant with a shoot length of 6.40 ±0.36cm. The root induction response is studied by aseptically transferring the shoots onto MS medium fortified with NAA, IBA, and IAA at varying concentration. Maximum root length and root number is recorded in MS supplemented with 1- Naphthalene Acetic Acid (NAA) at 0.5 mg L-1. However, a 100 % root induction frequency is observed in all the samples under study. The rooted plantlets are removed from the culture flasks and transferred into hardening media containing 1:1:1 ratio of Sand: Soil: Cocopeat. The hardened plants are healthy and disease-free and showed a 92% survival after acclimatization.